Response to Tibayrenc and Ayala: Reproductive clonality in protozoan pathogens - Truth or artefact? (2015)
Tibayrenc and Ayala raised several interesting objections to an opinion piece we recently published in Molecular Ecology (Ramirez and Llewellyn 2014). Our piece examined the value of an alternative perspective to their theory of predominant clonal evolution (PCE) on the prevalence and importance of genetic exchange in parasitic protozoa. In particular, our aim was to establish whether population genetic signatures of clonality in parasites were representative of true biological/evolutionary processes or artefacts of inadequate tools and inappropriate or inadequate sampling. We address Tibayrenc and Ayala's criticisms and make a detailed response. In doing so, we deny the consensus that Tibayrenc and Ayala claim around their views and dismiss much of the language which Tibayrenc and Ayala have introduced to this debate as either arbitrary or inaccurate. We strongly reject accusations that we misunderstood and misquoted the work of others. We do not think the PCE provides a useful framework for understanding existing parasite population structures. Furthermore, on the eve of the population genomic era, we strongly urge Tibayrenc and Ayala to wait for the forthcoming wealth of high-resolution data before considering whether it is appropriate to refine or re-iterate their PCE hypothesis. © 2015 John Wiley and Sons Ltd.